Contribution to the knowledge of the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) in China - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2015)
Two new species of the ant-like stone beetle genus Syndicus Motschulsky (Scydmaeninae: Cyrtoscydmini) from the Hainan Island, southern China are described: S. (Semisyndicus) grossepunctatus sp. n. and S. (Semisyndicus) hainanicus sp. n. The previously unknown female of S. (Semisyndicus) schuelkei is discovered, and its spermatheca is illustrated. Syndicus (s. str.) jaloszynskii is newly recorded from Hunan, central China. A single female of the nominotypical subgenus from Motuo, Xizang is listed; its identity remains unconfirmed until associated males become available.